CALCULATION OF PIERCING FORCE AT PRODUCTION OF TUBE - V. I. Timoshpoiski; V. V. Klubovich; G. M. Zhdanovich; L. A. Isajevich; V. A. Tomilo (Литьë и металлургия, 2007)
Force parameters of drifting cylindrical stock materials process by a mandrel plugging sections of cylindrical, conic, spherical and paraboloidal surfaces are certain.